Re-exposition to ipilimumab plus nivolumab in metastatic Merkel cell carcinoma - Valerie Glutsch; Patrick Schummer; Matthias Goebeler; Anja Gesierich; Bastian Schilling; Bastian Schilling (Frontiers in Immunology)
BackgroundMerkel cell carcinoma (MCC) is a rare but highly aggressive cutaneous malignancy. Immune checkpoint inhibition (ICI) with PD-(L)1 blockade has significantly improved treatment outcomes in metastatic disease. In patients with primary resistance to PD-(L)1 inhibition, a high overall response rate (ORR) of 50% to later-line ipilimumab plus nivolumab (IPI/NIVO) has been demonstrated. However, clinical data on patients with progression after an initial response to IPI/NIVO are still lacking.MethodsClinical data of three metastatic MCC patients who were re-exposed to IPI/NIVO after progression were retrospectively evaluated.ResultsTwo of the three patients showed primary resistance to avelumab with progressive disease, while one patient showed complete response (according to RECIST V.1.1). All three patients received combined ICI with IPI/NIVO as subsequent therapy, resulting in an ORR of ∼ 67%. However, all three patients progressed during follow-up and were re-exposed to IPI/NIVO. With a follow-up period ranging from 6.5 to 37.1 months, no PFS event has been detected. ORR for IPI/NIVO re-exposition was equal to that of initial IPI/NIVO treatment.ConclusionIn this retrospective follow-up analysis, we observed a response rate of 67% and long-lasting responses after re-exposition to combined ICI in metastatic MCC patients with progression after initial response or disease control upon their first IPI/NIVO treatment. An important observation from this small analysis is that primary resistance to PD-L1 inhibition may result in a better response to IPI/NIVO.